Cyclic Oligosaccharide-Based Chiral Stationary Phases Applicable to Drug Purity Control; A Review - Kalikova, Kveta; Slechtova, Tereza; Tesarova, Eva (Current medicinal chemistry, 2017)
Oligosaccharide-based chiral stationary phases are frequently used for enantioselective separations by different chromatographic techniques, namely gas chromatography, high performance liquid chromatography, supercritical fluid chromatography or capillary electrochromatography. Their multimodal application potential (they are compatible with both polar and/or non-polar mobile phases) makes them suitable chiral selector candidates for separation of a wide variety of structurally diverse compounds. In this paper, separation systems utilizing cyclodextrin- or cyclofructan-based chiral stationary phases in analyses of pharmacologically active compounds are summarized. The review covers the period from 2000 to 2015. This review article can be helpful to analysts searching for an appropriate method for the separation/determination of pharmaceuticals of their interest.
Keywords: Chromatography, Gas; chromatografie plynová; Pharmaceutical Preparations; drugs; enantioseparation; Cyclodextrin; léčivé přípravky; Chromatography, High Pressure Liquid; pharmaceuticals; oligosacharidy; enantioselectivity; vysokoúčinná kapalinová chromatografie; chromatography; cyclofructan; Oligosaccharides